Botany, Traditional Use, Phytochemistry, Pharmacology and Quality Control of Taraxaci herba: Comprehensive Review - Jianhao Wu; Jialin Sun; Meiqi Liu; Xiaozhuang Zhang; Lingyang Kong; Lengleng Ma; Shan Jiang; Xiubo Liu; Wei Ma (MDPI AG, 2024)
Taraxaci herba, as a traditional Chinese medicine, is the name of the Taraxacum genus in the Asteraceae family. Documented in the Tang Herbal Medicine (Tang Dynasty, AD 657-659), its medicinal properties cover a wide range of applications such as acute mastitis, lung abscess, conjunctival congestion, sore throat, damp-heat jaundice, and vision improvement. In the Chinese Pharmacopoeia (Edition 2020), more than 40 kinds of China-patented drugs containing Taraxaci herba were recorded. This review explores the evolving scientific understanding of Taraxaci herba, covering facets of ethnopharmacology, botany, phytochemistry, pharmacology, artificial cultivation, and quality control. In particular, the chemical constituents and pharmacological research are reviewed. Taraxaci herba has been certified as a traditional medicine plant, and its flavonoids, phenolic acids, and terpenoids have been identified and separated, which include Chicoric acid, taraxasterol, Taraxasteryl acetate, Chlorogenic acid, isorhamnetin, and luteolin; they are responsible for anti-inflammatory, antioxidant, antibacterial, anti-tumor, and anti-cancer activities. These findings validate the traditional uses of Taraxaci herba and lay the groundwork for further scientific exploration. The sources used in this study include Web of Science, Pubmed, the CNKI site, classic monographs, the Chinese Pharmacopoeia, the Chinese Medicine Dictionary, and doctoral and master's theses.